A simple Bayesian method for assessing the standard error of equivalent dose estimates - Peng, Jun; Dong, ZhiBao (Ancient TL, 2014)
Estimating the equivalent dose (ED) value is critical to obtaining the burial dose for Optically Stimulated Luminescence (OSL) dating. In this study, a simple Bayesian method is used to assess the standard error of an ED value in a linear or an exponential model. An ED value is treated as a stochastic node that depends on a random variable whose posterior distribution can be constructed and sampled. The results show that the Bayesian approach may improve the precision of an ED estimate by avoiding the repeated curve-fitting procedure employed in the routine “parametric bootstrap” Monte Carlo method.